2018
DOI: 10.1097/md.0000000000010129
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of postoperative coagulation profiles and outcome for sugammadex versus pyridostigmine in 992 living donors after living-donor hepatectomy

Abstract: Donor safety is the major concern in living donor liver transplantation, although hepatic resection may be associated with postoperative coagulopathy. Recently, the use of sugammadex has been gradually increased, but sugammadex is known to prolong prothrombin time (PT) and activated partial thromboplastin time (aPTT). We compared the postoperative coagulation profiles and outcomes of sugammadex versus pyridostigmine group in donors receiving living donor hepatectomy.Consecutive donor hepatectomy performed betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Moon et al compared postoperative coagulation profiles in living donors undergoing hepatectomy [ 18 ]. The two patient groups received either sugammadex 4 mg/kg or pyridostigmine 0.25 mg/.kg to reverse rocuronium-induced neuromuscular blockade.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Moon et al compared postoperative coagulation profiles in living donors undergoing hepatectomy [ 18 ]. The two patient groups received either sugammadex 4 mg/kg or pyridostigmine 0.25 mg/.kg to reverse rocuronium-induced neuromuscular blockade.…”
Section: Reviewmentioning
confidence: 99%
“…According to Table 1 , three out of nine studies were randomized crossover trials [ 8 - 9 , 20 ], two were randomized controlled trials [ 19 , 21 ], one was a randomized trial without a control group [ 23 ], two were prospective observational studies [ 17 , 22 ], and one was a retrospective observational study [ 18 ]. In three out of nine trials, sugammadex was used in the dosage of 4 mg/kg [ 9 , 18 , 21 ], in three out of nine trials the sugammadex dosage was 2 mg/kg and 4 mg/kg [ 17 , 22 - 23 ], in two out of nine trials, sugammadex 4 mg/kg and 16 mg/kg were used [ 8 , 20 ], and finally, in one out of nine, the dosage for sugammadex was 2 mg/kg [ 19 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…It was first introduced by the scientific community in 2002; since then, both animal and human studies have demonstrated the efficacy and tolerability of this drug [5, 6]. Additionally, from the time that this drug was introduced, several adverse events that are related to the use of sugammadex, including coagulation disorders, have been reported [7–9]. In vitro experiments have demonstrated that sugammadex influences the effects of factor Xa in the coagulation pathway, which then leads to the inhibition of the prothrombine-to-thrombin conversion [10].…”
Section: Introductionmentioning
confidence: 99%